ANALYSIS OF STUDENTS’ ERRORS OF CLASS VIII MTs ATH-THOHIRIYYAH IN SOLVING CIRCLE MATERIAL PROBLEMS BASED ON NOLTING THEORY - Aini Zulfa Izza; Dewi Mardhiyana (IAIN Ambon, 2022)
This research is a qualitative descriptive research that aims to describe the types of student errors and the factors that cause students making mistakes in solving problems about circle material based on Nolting's theory. This research involved 25 students of class VIII B MTs Ath-Thohiriyyah Watusalam for the academic year 2021/2022 through test and interview methods. The results showed the types of student errors were: 65.6% concept errors, 63.2% test-taking errors, 57.6% misread-directions errors, 56% careless errors, 8% study errors, and 6.4% application errors. Factors that cause students making mistakes because of they are nervous, don’t understand the questions, don’t study before doing the test, don’t take care, don’t recheck the answers before they are collected, don’t understand the formula, don’t understand the operating steps, dislike mathematics, and study habits by skimming. without understanding.